PENGARUH ASET PERUSAHAAN, PAJAK PENGHASILAN, DAN MEKANISME CORPORATE GOVERNANCE TERHADAP MANAJEMEN LABA - Jannah, Avin Mar’atul; Mildawati, Titik (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis research is meant to test the influence of company assets, income tax, and corporategovernance mechanism to the earnings management on consumer goods sector manufacturing companies which are listed in Indonesia Stock Exchange (IDX) in 2013-2015 periods. The method has been done by using purposive sampling method and this research is quantitative. The data is the secondary data which is the financial statement and company annual statement. The numbers of samples in this research are 72 observation objects. The analysis method has been carried out by using multiple linear regressions analysis and the SPSS 23rd version application. Based on the result of the research, it shows that the company assets which is proxy by firm size gives positive influence to the earnings management. The income tax gives negative influence to the earnings management. The corporate governance mechanism is proxy by institutional ownership, managerial ownership gives positive influence to the earnings management whereas the proportion of board of independent commissioner and audit committee does not give any influence to the earnings management.Keywords: company assets, income tax, corporate governance mechanism, earnings management.